Frequency of Urinary Tract Infection among Neonates with Persistent Jaundice at Lady Reading Hospital, Peshawar : Frequency of Urinary Tract Infection among Neonates - Muhammad, Lal; Khan, Inayatullah; Khan, Afzal; Numan, .; Hussain, Saddam; Ali, Sajid (Pakistan Journal of Health Sciences, 2024)
Jaundice refers to yellow-orange discoloration of the skin and sclera, resulting from an excessive accumulation of bilirubin in the dermis and mucous membranes. Indirect neonatal hyperbilirubinemia is a prevalent and frequent etiology of jaundice, leading to the hospitalization of neonates in healthcare institutions worldwide. Objective: To determine the frequency of urinary tract infection among neonates with prolonged jaundice. Methods: The present study, a cross-sectional design, was carried out at the Department of Pediatrics, Lady Reading Hospital, Peshawar, from June 20th to December 20th, 2022. The study consisted of 87 infants, encompassing both genders, who presented with persistent jaundice. Two samples of clean urine were collected from neonates, with a time interval of many minimums of two hours between each collection. These samples were then sent to the hospital laboratory for diagnosing urinary tract infection. Results: The age range of participant neonates in this study ranged from 14 to 28 days, with a mean age of 20.597±4.50 days. The mean duration of complaint was also 18.20±4.077 days, and the mean weight was 2.855±0.27 Kg. The proportion of male patients was 58.6%, while the proportion of female patients was 41.4%. Among these 11.5% were found to have urinary tract infection. Conclusions: It is concluded that significant number (11.5%) of patients with persistent jaundice has urinary tract infection. It is likely a potential etiological factor contributing to neonatal unexplained prolonged indirect hyperbilirubinemia.